Carer perspectives of a transition to adult care model for adolescents with an intellectual disability and/or autism spectrum disorder with mental health comorbidities. (18th August 2022) - Culnane, Evelyn; Efron, Daryl; Williams, Katrina; Marraffa, Catherine; Antolovich, Giuliana; Prakash, Chidambaram; Loftus, Hayley
Abstract: Background: Transition to adult care for adolescents with an intellectual disability and/or autism spectrum disorder with coexisting mental health disorders, often termed 'dual disability', is complex. It requires a family‐centred approach, with collaboration among health, disability and social services and early planning. Aim: To describe carer perspectives of transition to adult care and the outcomes of a transition support intervention, Fearless, Tearless Transition, for adolescents with dual disabilities piloted at a tertiary children's hospital. Methods: Carers of adolescents with a dual disability were invited to complete a survey at the commencement of their participation in the Fearless, Tearless Transition model, and again at the conclusion of the project. Within this intervention, carers and adolescents were encouraged to attend dedicated transition clinics and participate in a shared care general practitioner (GP) and paediatrician process. Results: One hundred and fifty‐one carers of adolescents with dual disabilities were included in Fearless, Tearless Transition . Of this cohort, 138 adolescents and their carers received support in a dedicated transition clinic with 99 carers completing the initial survey at the commencement of the model. Eighty‐two per cent of carers reported moderate to high levels of anxiety about transitioning from paediatric to adult care with 39% feeling 'unprepared' about transition. Eighty‐one per cent reported having inadequate access to respite care with 47% reporting a lack of access to services in the community and 56% expressing dissatisfaction with their GPs. One hundred and two families participated in the shared care process with 80 GPs and 33 paediatricians. Twenty‐two carers completed the second survey reporting a modest but significant improvement in preparedness for transition to adult care. Conclusion: This study highlights the potential to improve transition outcomes for adolescents with dual disabilities and their carers through early, centralized transition planning, consistent methods of assessing adolescent and carer needs and shared care.